European oak chemical diversity – from ecotypes to herbivore resistance. Issue 2 (5th August 2021) - Bertić, Marko; Schroeder, Hilke; Kersten, Birgit; Fladung, Matthias; Orgel, Franziska; Buegger, Franz; Schnitzler, Jörg‐Peter; Ghirardo, Andrea
Summary: Climate change is increasing insect pressure and forcing plants to adapt. Although chemotypic differentiation and phenotypic plasticity in spatially separated tree populations are known for decades, understanding their importance in herbivory resistance across forests remains challenging. We studied four oak forest stands in Germany using nontarget metabolomics, elemental analysis, and chemometrics and mapped the leaf metabolome of herbivore‐resistant (T‐) and herbivore‐susceptible (S‐) European oaks ( Quercus robur ) to Tortrix viridana, an oak pest that causes severe forest defoliation. Among the detected metabolites, we identified reliable metabolic biomarkers to distinguish S‐ and T‐oak trees. Chemotypic differentiation resulted in metabolic shifts of primary and secondary leaf metabolism. Across forests, T‐oaks allocate resources towards constitutive chemical defense enriched of polyphenolic compounds, e.g. the flavonoids kaempferol, kaempferol and quercetin glucosides, while S‐oaks towards growth‐promoting substances such as carbohydrates and amino‐acid derivatives. This extensive work across natural forests shows that oaks' resistance and susceptibility to herbivory are linked to growth‐defense trade‐offs of leaf metabolism. The discovery of biomarkers and the developed predictive model pave the way to understand Quercus robur 's susceptibility to herbivore attack and to support forest management, contributing to the preservation of oak forests in Europe.